RELASI DAN PERAN AKTOR DALAM PEMANFAATAN RPTRA KELURAHAN PEJAGALAN JAKARTA UTARA - Wahjudi, Sugeng (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
The development and optimization of RPTRA function as public space in Kelurahan Pejagalan generates clicks of communication nodes that make the utilization or maintenance of RPTRA complex and complicated. This research tries to reveal how role and relation of the actors in RPTRA management. The method used is the analysis of communication network patterns by making the matrix of communication relations between actors observed from the results of questionnaires and interview questions, sociometric analysis done by descriptive approach. These communication network data were analyzed with UCINET VI. The result of the research with the sociogram analysis showed that the average of individuals in the group had good connectivity with each other. Opinion leaders are still dominated by the formal leaders of Lurah and Ibu Lurah as well as RPTRA coordinator appointed and responsible to the lurah.Keywords: clicks, actor relation, sociometry, opinion leader